Gas viscosity mems sensor based on pull-in - Dias, R. A. (2013)
A novel method for measuring the viscosity of gases is introduced here, that uses a parallel-plate capacitive device, electrostatically actuated to pull-in. In welldefined actuation and damping conditions, the pull-in time is proportional to viscosity of the gas medium between the plates, since viscosity determines the damping level. MEMS structures have been fabricated to experimentally verify the method of using pull-in time to measure viscosity, and the results are encouraging. Different pure gases and gaseous mixtures, common in the natural gas industry, have been tested and the approached proved to be very sensitive (2000 μs/μPa.s) and the measured pull-in time variation with viscosity presents good linearity.